Nitrogen, Phosphorus, Carbon and Population. (December 2015) - Gilland, Bernard
Population growth makes food production increase necessary; economic growth increases demand for animal products and livestock feed. As further increase of the cropland area is ecologically undesirable, it is necessary to increase crop yields; this requires, inter alia, more nitrogen and phosphorus fertiliser, despite the environmental problems which this will exacerbate. It is probable that a satisfactory food supply and an environmentally benign agriculture worldwide cannot be achieved without reducing population to approximately three billion. The reduction could be achieved by 2200 if the total fertility rate - currently 2.5 - declined to 1.5 as a world average by 2050, and remained at that level until 2200, but the probability of such a global fertility trajectory is close to zero. It will also be necessary to replace fossil energy by nuclear and renewable energy in order to stabilise atmospheric carbon dioxide concentration, but the phase-out cannot be completed until the 22nd century, when the atmospheric concentration will be approximately 50% above the 2015 level of 400 ppm.